Competing Vegetation Effects on Soil Carbon and Nitrogen in a Douglas‐fir Plantation. Issue Volume 78:Issue Supplement 1(2014) (2nd May 2014) - Knight, Erika; Footen, Paul; Harrison, Robert; Terry, Thomas; Holub, Scott
Abstract : Application of herbicides to control competing vegetation and improve crop tree growth is a common silvicultural practice. Vegetation control has the potential to change pools of soil C and N and thus affect soil quality and C sequestration. In this study, the effects of vegetation control (primarily for herbaceous vegetation) on soil C and N were compared for a bole‐only harvest with and without 5 yr of annual herbicide application (+VC and −VC, respectively). Soil C and N were measured in six depth increments (forest floor and 0–15, 15–30, 30–45, 45–60, and 60–100 cm) in a 12‐yr‐old Douglas‐fir [ Pseudotsuga menziesii (Mirb.) Franco] plantation at the Fall River Long‐Term Soil Productivity site in western Washington. Deep‐soil (60–100‐cm) C concentration was significantly higher (α = 0.10) with vegetation control (14.7 g kg −1 for +VC, 10.4 g kg −1 for −VC). Nitrogen concentration was significantly higher in the forest floor treatment without vegetation control (11.2 g kg −1 N for +VC, 12.7 g kg −1 N for −VC); however, the N content of the −VC 0‐ to 15‐cm mineral soil was significantly lower than the +VC (2920 kg N ha −1 for +VC, 2720 kg N ha −1 for −VC). The root concentration (kg roots kg soil −1 ) was higher in the +VC treatment at both the 30‐ to 45‐ and 45‐ to 60‐cm depth intervals. Despite these differences, there were no significant differences in total C or N content to 100 cm with and without vegetation control. The longer term impact of the greater root concentration at 30 to 60 cm on soil C and N pools needs to be assessed.